Metallomic study on plasma samples from Nile tilapia using SR-XRF and GFAAS after separation by 2D PAGE: initial results - Santos, Felipe A. [UNESP]; Lima, Paula M. [UNESP]; Neves, Renato C. F. [UNESP]; Moraes, Paula M. [UNESP]; Perez, Carlos A.; Silva, Marcelo O. A.; Arruda, Marco A. Z.; Castro, Gustavo R. [UNESP]; Padilha, Pedro de Magalhaes [UNESP] (Springer Wien, 2011)
An investigation was made on plasma samples obtained after protein separation. The proteome of the plasma of Nile tilapia (Oreochromis niloticus) was separated by 2D PAGE, and manganese and zinc in protein spots was qualitatively and quantitatively determined by synchrotron radiation X-ray fluorescence (SR-XRF) and graphite furnace atomic absorption spectrometry (GFAAS). Manganese and zinc are present in four and six plasma protein spots, respectively. These ions are bound to proteins with molecular weights ranging from 19 to 70 kDa and with isoelectric point (pI) ranging from 4.7 to 6.3. The concentrations of manganese and zinc bound to these proteins as determined by GFAAS following acid digestion of the spots range from 0.8 to 2.6 mg of manganese, and from 1.0 to 6.3 mg of zinc, respectively, per g of protein.
Keywords: Metalloproteins; 2D PAGE; SR-XRF; GFAAS; Nile tilapia